Is heme biosynthesis influenced the mitochondrial function and cell proliferation in cancer? - Raisa Nauli; Sri Widia A Jusman (Acta Biochimica Indonesiana, 2022)
Heme is a compound consisting of an iron (Fe) atom bound to a pyrrole ring forming protoporphyrin IX (PPIX). Protoporphyrin combines with a protein-forming hemoprotein compound that plays an essential role in oxygen-binding and transport as well as in the process of energy production in the mitochondria. Some cancer cells have more heme biosynthesis than normal cells, which is thought to be linked to more cancer cell growth. Inhibition of heme biosynthesis in some cancer cells leads to decreased cell proliferation. This review article discusses the synthesis of heme, the role of heme in energy metabolism, which is needed for cell proliferation, the inhibition of heme synthesis and its effect on cancer cell proliferation, and the possibility of the inhibition of heme biosynthesis as an approach in therapy of cancer in the future.